Effect of Empagliflozin on Blood Volume Redistribution in Patients With Chronic Heart Failure and Reduced Ejection Fraction: An Analysis From the Empire HF Randomized Clinical Trial. (March 2022) - Omar, Massar; Jensen, Jesper; Burkhoff, Daniel; Frederiksen, Peter H.; Kistorp, Caroline; Videbæk, Lars; Poulsen, Mikael Kjær; Gustafsson, Finn; Køber, Lars; Borlaug, Barry A.; Schou, Morten; Møller, Jacob Eifer
Abstract : Background: Stressed blood volume (SBV) is a major determinant of systemic and pulmonary venous pressures which, in turn, determine left and right ventricular fillings and regulates cardiac output via the Frank-Starling mechanism. It is not known whether inhibition of the SGLT2 (sodium–glucose cotransporter-2) favorably affects SBV. We investigated the effect of empagliflozin on estimated SBV in patients with heart failure and reduced ejection fraction compared with placebo. Methods: This was a post hoc analysis of an investigator-initiated, double-blinded, placebo-controlled, randomized trial. Seventy patients were assigned to empagliflozin 10 mg or matching placebo once daily for 12 weeks. Patients underwent right heart catheterization at rest and during exercise at baseline and follow-up. The outcome was change in estimated SBV after 12 weeks of empagliflozin treatment over the full range of exercise, determined using a recently introduced analytical approach based on invasive hemodynamic assessment. Results: Patients with heart failure and reduced ejection fraction, mean age, 57 years and mean ejection fraction 27%, with 47 patients (71%) receiving diuretics were randomized. The effect of empagliflozin on estimated SBV over the full range of exercise loads showed a statistically significant reduction compared with placebo (−198.4 mL [95% CI, −317.4 to −79.3] P =0.001), a 9% decrease. The decrease in estimated SBV by empagliflozin was significantly correlated with the decrease in PCWP ( R =−0.33, P <0.0001). The effect of empagliflozin was consistent across subgroup analysis. Conclusions: Empagliflozin treatment significantly reduced SBV compared with placebo after 12 weeks of treatment in patients with stable chronic heart failure and reduced ejection fraction during sub maximal exercise. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03198585.